Larval traits of the Caribbean amphidromous goby Sicydium punctatum (Gobioidei: Sicydiinae) in Guadeloupe. Issue 2 (17th December 2014) - Lejeune, Léa; Tabouret, Hélène; Taillebois, Laura; Monti, Dominique; Keith, Philippe
Abstract: Amphidromous fish are the biggest contributor to the diversity of fish communities in river systems of Caribbean islands. Among them, Sicydium punctatum Perugia, 1896, which is endemic to the West Indies, represents the vast majority of fish in these rivers. The otolith microstructure and the biometry of S. punctatum postlarvae from Guadeloupe were investigated to explore the dispersal modalities of this species through an appreciation of the growth pattern, the pelagic larval duration (PLD) and the size‐at‐recruitment. The study was made on one cohort of 83 recruited postlarvae, fished at the Capesterre River's mouth on 2 November 2011. The mean (±SD) size‐at‐recruitment of the postlarvae was 24.6 ± 1.3 mm (range of 20.5–28.1 mm, n = 83). We found a mean (±SD) PLD of 72.2 ± 10.5 days (range of 54–101.5 days, n = 67). The growth rate estimated from the otolith increments showed a globally decreasing pattern during the marine larval phase. Growth rates at the beginning of the larval stage were significantly different between hatching periods, suggesting a relation between the hatching period and the growth rate in S. punctatum . This study adds on to the general understanding of the life cycle of S. punctatum in Guadeloupe that will help implement strategies to manage amphidromous fish populations in the Caribbean region.